The Influence of Product Quality and Service Quality on Customer Satisfaction at Mitra 10 in Depok - Susanti, Neneng; Jasmani, Jasmani (Universitas Negeri Makassar, 2019)
This study aims to determine the effect of product quality and service quality on customer satisfaction at Mitra 10 in Depok. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study product quality have a significant effect on customer satisfaction by 41.6%, hypothesis testing obtained significance 0,000 <0.05. Service quality has a significant effect on customer satisfaction by 42.7%, hypothesis testing obtained significance 0,000 <0.05. Product quality and service quality simultaneously have a significant effect on customer satisfaction by 52.3%, hypothesis testing obtained significance of 0,000 <0.05.